4 good reasons why - Butler, G. ; Bourne, F. ; Green, J. W. ; Gowridge, T. ; Whitehead, A. S. ; Abell, William H. ; Pickard, J. G.; Corah, John Reginald
1938-10 1938 1930s 12 pages The Day Staff — Leicester Royal Infirmary. It is the policy of the Board of Governors to reduce the Nurses' working hours to 96 a fortnight. This reform, long overdue, together with the inevitable future expansion of the work in all departments makes it apparent that an increased staff will be necessary. [photograph of nurses] DO YOU REALISE THE NUMBER OF PATIENTS TREATED ANNUALLY IN THE PRINCIPAL DEPARTMENTS OF THE ROYAL INFIRMARY? These figures for last year will bring home to you THE SERVICE OF THE NURSES. 9,242 In-Patients. 83,131 Attendances Out-Patient Department. 12,127 Operations. 47,433 Attendances Orthopaedic Department. 128,137 Attendances Casualty Department. 37,959 Attendances X-Ray Department. 292/842/2/106